Biomonitoring of radioactive contamination using benthic invertebrate communities in Manzala Lake, Egypt - Imam Noha; Bendary Reda E. (Oceanological and Hydrobiological Studies)
Manzala Lake, the largest in Egypt’s Nile Delta, has significant human activity. The Lake’s ecological condition has recently been impacted by a significant increase in agricultural, industrial, and urban wastewater discharge. A valuable tool for monitoring the water quality of Manzala Lake is the sensitivity of invertebrate species to various types of pollution, such as radioactive contamination. Activity concentrations of radionuclides Radium-226 (226Ra), Thorium-232 (232Th), Potassium-40 (40K), and Caesium-137 (137Cs) were measured in water, sediments and benthic invertebrate samples in 2020. The benthic community’s spatial distribution and the radionuclides’ bioaccumulation were evaluated to determine possible relationships. Thirty taxa of benthic invertebrates were recognised. The data illustrated that the mean activity concentration of radionuclides in water was in the order of 40K > 232Th > 226Ra > 137Cs, which changed into 40K > 226Ra > 232Th > 137Cs in the sediment and benthic invertebrates. Gastropoda and Ostracoda are the dominating groups of benthos in the lake and are related to the highest concentrations of radionuclides. The benthos species with shells dominated at the sites with the highest activity concentration of 226Ra, while soft-bodied organisms dominated in sites with the highest average 137Cs activity in these samples.